Partial Hydrogenation of Sunflower and Soybean Oil Over Zirconia Supported Platinum Catalyst - Kainaubek Toshtay (Bulletin of Chemical Reaction Engineering & Catalysis, 2025)
1.0% Pt/ZrO₂ catalyst was synthesized and thoroughly characterized to evaluate its structural, morphological, and surface properties, as well as its catalytic performance in the selective hydrogenation of sunflower and soybean oils. XRD analysis confirmed the formation of mixed monoclinic and tetragonal zirconia phases, with platinum highly dispersed on the support. Nitrogen adsorption–desorption studies revealed a surface area of 25.0 m²/g and an average pore diameter of 19.0 nm. SEM and TEM analyses showed nanosized particles (55–100 nm) with uniformly distributed Pt nanoparticles (2–8 nm). XPS spectra identified Pt⁰, Pt²⁺, and Pt⁴⁺ oxidation states, while TPR-H₂ and TPD-H₂ profiles demonstrated strong metal–support interaction and the predominance of weakly bound hydrogen species conducive to selective hydrogenation. Catalytic tests showed that the 1.0% Pt/ZrO₂ catalyst enabled partial hydrogenation of sunflower and soybean oils at 90 °C and 0.5 MPa, achieving high activity and low trans-isomer contents (6.0% and 5.6%, respectively). Compared with conventional Ni catalysts, which require higher temperatures (130–150 °C) and generate over 25% trans-isomers, the Pt-based system exhibited superior selectivity and energy efficiency. The catalyst retained its activity and selectivity over eight reuse cycles, maintaining stable structure and low trans-isomer formation. The resulting hydrogenated products met international regulations (<2.0% trans-isomers in final fat blends) and displayed favorable solid fat contents for food applications. These results demonstrate that the 1.0% Pt/ZrO₂ catalyst is an efficient, selective, and reusable system for producing high-quality, trans-fat–compliant hydrogenated oils under mild operating conditions. Copyright © 2025 by Authors, Published by BCREC Publishing Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).